KARAKTERISTIK PRINSIP KETERBUKAAN DALAM HUKUM PASAR MODAL DI INDONESIA - Asih K.Tus., Desyanti Suka (Fakultas Hukum Universitas Mahasaraswati Denpasar, 2016)
The role of the capital market for economic development in Indonesia is increasingly important existence. Society is increasingly showing interest to invest in the stock market. Foreigners are participate in the capital market to invest in Indonesianâscompanies. The existence of Law No. 8 of 1995 is intended to ensure the parties have activities in the capital market. The law also regulates the principles of capital market openness which is a general guideline that requires listed companies, public companies, and other parties subject to this law to inform the public in a timely manner all information material regarding its business or effects that can influence the decisions of investors to and the intended effect, or the price and securities. The principle of openness aims to create an efficient market mechanism. Due to the implementation of obligations of disclosure can prevent or at least the events that can lead to bad consequences for public investors. For the implementation of the obligation of openness makes investors can gain access to the right information or material facts